Analisis Teks Deskripsi dalam Buku Paket Piwulangan Bahasa Jawa Muatan Lokal Wajib Jawa Tengah Kelas VIII - Kurnianingrum, Aprilia; Sulanjari, Bambang (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2025)
This study aims to describe and explain about analyzing social functions and goals in the Origin Blora text, analyzing the stages of the descriptive text in the Blora Origin text, analyzing the linguistic characteristics of the descriptive text in the Blora Origin text. In this study using descriptive qualitative. This research provides detailed description and analysis of information. This research uses a single case study strategy which is carried out on one characteristic and one target (subject), namely the folklore of Blora Regency. The analysis technique used is interactive model of analysis. The folklore of Blora Regency is classified as legend, namely in individual legends and legends of the origin of a place. The results of the research on the Central Java Compulsory Local Content Package Book of Javanese Language Piwulangan Class VIII are considered suitable to be used as learning resources for class VIII students. It contains the social function or purpose of the test, stages containing the structure of the text and the linguistic features of the descriptive text which include the use of conjunctions, verbs, adverbs of time, and point of view.